Three-dimensional interconnected nitrogen-doped mesoporous carbons as active electrode materials for application in electrocatalytic oxygen reduction and supercapacitors - Lin, Gaoxin; Ma, Ruguang; Zhou, Yao; Hu, Chun; Yang, Minghui; Liu, Qian; Kaskel, Stefan; Wang, Jiacheng (Journal of Colloid and Interface Science, 2018)
In this paper, a series of nitrogen-doped mesoporous carbons (NMCs) with three-dimensional (3D) interconnected mesopores have been prepared using flour as carbon source, dicyanamide as nitrogen source and colloidal silica as hard template. The optimized material (NMC-4) prepared with the colloidal silica/flour mass ratio of 4 has a high nitrogen doping level of 5.69 at.% and large specific surface area of 995 m2 g−1 as well as 3D interconnected mesopores (12.9 nm). As the oxygen reduction reaction (ORR) electrocatalyst among various NMCs, NMC-4 exhibits the superior performance and much better stability and methanol crossover with a four-electron dominant reaction pathway compared to commercial 20 wt% Pt/C. Furthermore, as a supercapacitor (SC) electrode material, NMC-4 exhibits a high specific capacitance of 178.5 F g−1 at a current density of 0.5 A g−1 and long cycle life (94.5% capacity retention after 5000 cycles). It also shows a good rate capacity as 76.1% of original specific capacitance remains when the current density increases from 0.5 to 20 A g−1. The high-performance of NMCs results from the synergetic effects of 3D interconnected mesopores, large surface area, and high N-doping level, enabling fast mass transport and electron transfer during the electrochemical process. This work provides a facile and efficient strategy to heteroatom-doped carbons from extensively available biomass, showing great potentials in electrocatalysis, energy storage, and other applications.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Biomass; Electrocatalysis; Energy storage; Nitrogen-doped carbons; Three-dimensional interconnected mesopores